Long-Term Follow-Up Results of Fecal Microbiota Transplantation for Irritable Bowel Syndrome: A Single-Center, Retrospective Study - Cui, Jiaqu; Lin, Zhiliang; Tian, Hongliang; Yang, Bo; Zhao, Di; Ye, Chen; Li, Ning; Qin, Huanlong; Chen, Qiyi (Frontiers in Medicine, 2021)
Objective: Our aim was to investigate long-term efficacy of fecal microbiota transplantation (FMT) in patients with irritable bowel syndrome (IBS). Study Methods: A single-center long-term follow-up study was performed in patients who received FMT for moderate-to-severe IBS (IBS-severity scoring system (IBS-SSS) >175). After 1 year of FMT treatment, decide whether to repeat FMT based on IBS-SSS (IBS-SSS >175). Pre-FMT and post-FMT baseline characteristics and questionnaires were completed at 1 month, 3 months, 6 months, 12 months, 24 months, 36 months, 48 months and 60 months after FMT. Study outcomes included effective rates, the change of IBS-SSS, IBS-specific quality of life and fatigue, the effect on stool frequency and Bristol Stool Scale for IBS-C and IBS-D, and side effect. Results: A total of 227 patients (47.58% IBS-C, 39.21% IBS-D and 13.22% IBS-M) were included (142 females and mean age 41.89 ± 13.57 y). The effective rates were 108(51.92%), 147 (74.62%), 125 (74.41 %), 88 (71.54%), 78 (75.00%), 65 (73.03%), 45 (61.64%) and 37 (62.71%) respectively at different follow-up time points. Total IBS-SSS score was 321.37 ± 73.89 before FMT and significantly decreased after 1 month. The score of IBS-QoL was 40.24 ± 11.34 before FMT, and increased gradually and it was significantly higher at 3 months than pre-FMT. The total FAS score was 47 ± 8.64 before FMT and it was significantly lower at 3 months. During the follow-up, 89（39.21%）side effects occurred. These symptoms were cured by symptomatic treatment and no serious adverse events were found during follow-up. Conclusion: After 60 months of long-term follow-up, it was found that FMT was safe and effective for IBS. However, the treatment effect will decline over time, periodic and repetitive FMT is needed to maintain the effect.